Controllability of conformable differential systems - Wang, Xiaowen; Wang, JinRong; Fečkan, Michal (Nonlinear Analysis: Modelling and Control, 2020)
This paper deals with complete controllability of systems governed by linear and semilinear conformable differential equations. By establishing conformable Gram criterion and rank criterion, we give sufficient and necessary conditions to examine that a linear conformable system is null completely controllable. Further, we apply Krasnoselskii’s fixed point theorem to derive a completely controllability result for a semilinear conformable system. Finally, three numerical examples are given to illustrate our theoretical results.